2013
DOI: 10.3329/sjm.v2i1.15212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasmid curing on Rhizobium spp.

Abstract: Present study was carried out to determine the difference between the wild type rhizobial strains and plasmid cured strains for some important characteristics such as antibiotic resistance. The rhizobial strains were isolated from locally produced legumes of different varieties such as Pisum sativum, Sesbania aculeata, Vigna mungo, Phaseolus vulgaris, Lens culinaris and Arachis hypogea.They were purified and subjected to various morphological, cultural and biochemical analysis, and also to antibiogram. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…In general, all the isolates harbored one plasmid with size of 10 kb, while two isolates (RLB of Benisuef and RLG of Giza) contained an additional plasmid with size of 2 kb ( Figure 3A). These results are in agreement with previous studies have shown that most of the Rhizobial species harbour plasmids that vary in number (1 to 10) and in size [39,40]. Two restriction endonucleases, MspI and ECORI were used to digest the plasmids and studying their restriction profiles.…”
Section: Molecular Characterization Of Rlv Isolatessupporting
confidence: 91%
“…In general, all the isolates harbored one plasmid with size of 10 kb, while two isolates (RLB of Benisuef and RLG of Giza) contained an additional plasmid with size of 2 kb ( Figure 3A). These results are in agreement with previous studies have shown that most of the Rhizobial species harbour plasmids that vary in number (1 to 10) and in size [39,40]. Two restriction endonucleases, MspI and ECORI were used to digest the plasmids and studying their restriction profiles.…”
Section: Molecular Characterization Of Rlv Isolatessupporting
confidence: 91%
“…Where it was noted that all bacteria isolates were 100% resistant to Trimethoprim and Streptomycin, as for the antibiotics Rifampicin and Tetracycline, the resistance was less than it was 22.2 % among the groups of isolates understudy, while the percentage differences in resistance to other antibiotics of the bacterial isolates in the study amounted to 88.8 % in Erythromycin and Amoxicillin, and in Nystatin the percentage reached 77.7%, and the percentage in Ampicillin reached 77.7%, while the percentage in Gentamycin was 33.3%, and the percentage in Cefixime was 88.8%. The results of this study were the same as what the researcher discovered [41]. In terms of the resistance of most of the isolates to the antibiotic Amoxicillin, where the results of Rhizobium resistance to Tetracycline,Streptomycin, Amoxicillin, and Ampicillin converged with many studies that indicated Rhizobium possessing resistance to these antibiotics and several isolates of Sinorhizobium meliloti and R. Leguminosarum, [42] [43].…”
Section: Resistance and Sensitivity Test Of Bacteria Isolated From Root Nodules To Antibioticssupporting
confidence: 77%